1973
DOI: 10.1084/jem.138.3.574
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of Replication in Lymphoid Cells by Specific Thiols and Disulfides in Vitro

Abstract: Lymphocyte division has been the subject of many studies from the point of view of cellular immunology and antibody synthesis. Blast cell transformation and mitosis occur both in vitro and in vivo under stimulus from a number of agents which act on the cell surface, particularly in experimental situations by lectins (1).Although the sequence of events which connect the mitogenic stimulus to DNA synthesis is still incompletely known and several different cell types may be involved, a nmnber of preliminary chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
0
1

Year Published

1975
1975
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 211 publications
(83 citation statements)
references
References 24 publications
7
74
0
1
Order By: Relevance
“…Previous studies [6][7][8] and also this study showed that the addition of thiol compounds, including meso-DMSA and DMPS, enhanced the proliferative response to Con A and LPS. It is believed that effects of thiol compounds on the activities of lymphocytes are due to the low redox potential of thiol compounds to either maintain monothiols completely in a reduced state on cell surface proteins or to interrupt disulfide bonds between cell membrane proteins [6,28,29].…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Previous studies [6][7][8] and also this study showed that the addition of thiol compounds, including meso-DMSA and DMPS, enhanced the proliferative response to Con A and LPS. It is believed that effects of thiol compounds on the activities of lymphocytes are due to the low redox potential of thiol compounds to either maintain monothiols completely in a reduced state on cell surface proteins or to interrupt disulfide bonds between cell membrane proteins [6,28,29].…”
Section: Discussionsupporting
confidence: 70%
“…Previous studies [6][7][8] and also this study showed that the addition of thiol compounds, including meso-DMSA and DMPS, enhanced the proliferative response to Con A and LPS. It is believed that effects of thiol compounds on the activities of lymphocytes are due to the low redox potential of thiol compounds to either maintain monothiols completely in a reduced state on cell surface proteins or to interrupt disulfide bonds between cell membrane proteins [6,28,29]. Such modulation on lymphocyte activities has been found to be related to chemical structure of thiol compounds [6], in which the substitution of non-thiol group on thiol compounds with other functional groups may alter the activity of the molecule [6,29].…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, a considerable proportion of the cells were observed to have less RNA than 0-time cells. Since murine spleen cells characteristically do poorly in cell culture (4,12), these cells were probably either dead or dying at the time of fixation. Few cells with greater than 0-time RNA contents were observed.…”
Section: Methodsmentioning
confidence: 99%